2021
DOI: 10.3389/fnins.2021.712462
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Children With Vasovagal Syncope Is Associated With Impaired Circadian Rhythm of Blood Pressure

Abstract: BackgroundVitamin D deficiency is associated with the risk of cardiovascular diseases. We aimed to investigate the serum vitamin D levels in children with vasovagal syncope (VVS) and explore the correlation of vitamin D status and circadian rhythm of blood pressure in VVS pediatric patients.MethodsThis was a retrospective study. 130 syncopal children diagnosed with VVS were included in the study. 110 age and gender matched healthy individuals were enrolled as control. According to serum 25(OH)D levels, VVS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This study indicates that vitamin D deficiency was common among children and adolescents with syncope and demonstrates a prevalence of 60.0% in the VVS group, 54.2% in the group of syncope due to OH, and 47.4% in the group of CS which are not statistically different. These results are partially comparable with other studies of 25(OH)D levels in children with VVS which showed that 33.8% had vitamin D deficiency 19 and 60.0% 14 and suggested that 25(OH)D may be involved in the pathological mechanism of different syncope types by affecting cardiac autonomic function.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study indicates that vitamin D deficiency was common among children and adolescents with syncope and demonstrates a prevalence of 60.0% in the VVS group, 54.2% in the group of syncope due to OH, and 47.4% in the group of CS which are not statistically different. These results are partially comparable with other studies of 25(OH)D levels in children with VVS which showed that 33.8% had vitamin D deficiency 19 and 60.0% 14 and suggested that 25(OH)D may be involved in the pathological mechanism of different syncope types by affecting cardiac autonomic function.…”
Section: Discussionsupporting
confidence: 90%
“…Some recent studies have shown that VVS in children is associated with reasonably low vitamin D levels. 14 , 19 Gialini et al 20 reported an association between probability of OH and circulating vitamin D levels in elderly males. Despite this fact, Laird et al 21 published another study results in which the authors described that vitamin D concentration was not significantly associated with OH in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Egger's and Begg's 22,23 Duplicates were removed (n = 89) and the remaining 365 went through the first screening using titles/abstracts after which 25 studies underwent full-text screening. Finally, six studies 14,15,[24][25][26][27] remained to be included in our systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…There was a total of 954 individuals assessed in these studies. Four studies were conducted in China 15,24,26,27 and the design of all but one of them 24 was a retrospective cohort.…”
Section: Discussionmentioning
confidence: 99%